The Agrobacterium rhizogenes oncogenes rolB and ORF13 increase formation of generative shoots and induce dwarfism in Arabidopsis thaliana (L.) Heynh - Kodahl, Nete (Plant science : an international journal of experimental plant biology, 2016)
Copyright © 2016 Elsevier Ireland Ltd. All rights reserved.